ANALISIS PENGELOLAAN SAMPAH PADAT DI KOTA TANGERANG SELATAN - Serena Mastuti (FT-USNI, 2018)
Waste management in South Tangerang City is carried out by the Environmental Waste Sector. Waste transportation is carried out by the Environmental Service and the appointed private sector. Waste transportation is carried out starting from the garbage source to the Temporary Disposal Site and the garbage is transported by garbage trucks to the Cipeucang Final Disposal Site. Waste transportation is carried out 2 rays / day where transportation using a cart from the garbage source to the TPS and / or TPS3R takes 280 minutes / rit and the cost of using a garbage truck from TPS and / or TPS3R takes 400 minutes / rit. But the problem that arises is that the waste generation in the community is not fully transported to the landfill. The purpose of this study was to determine the flow of waste management in South Tangerang City, and to find out the efforts made by the Environmental Agency in the Waste Sector to reduce the burden of waste at the Cipeucang Landfill. This research is classified into the type of qualitative descriptive research with a naturalistic approach method which describes in detail based on the facts that exist. The sampling technique is by using Purposive Sampling techniques. The conclusion of this research is that the waste management carried out by the South Tangerang City Environmental Agency is still not optimal, garbage transportation is still constrained by the large number of damaged garbage transport fleets, the absence of segregation of waste from garbage sources, and insufficient human resources or waste management officers in South Tangerang City.